2013
DOI: 10.1111/eth.12189
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Male Dominance on Egg Testosterone and Antibacterial Substances in the Egg of Grey Partridges

Abstract: International audienceMaternal effects play an important role in mediating reproductive success; the different allocation of resources in eggs is considered a primary maternal effect. In oviparous vertebrates, there are several substances (hormones, immunoglobulins, antioxidants, antibacterial molecules) that females may allocate differentially. Mate choice is a key factor influencing female reproductive decisions and investment in eggs, but it is not clear to what extent the dominance status of the partner ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…Third, aggression may influence paternity gain and loss if it is coupled with ejaculate quality (Rojas Mora et al 2017), mate guarding and/or copulation frequency (Ophir et al 2005) and/or extrapair activity (Spoon et al 2007;van Oers et al 2008). Lastly, aggression may influence hatching and fledging success either via nest-site quality (see above), differential maternal allocation (Grenna et al 2014;Szász et al 2014) or paternal provisioning, which can be negatively related to aggression (Duckworth 2006;Mutzel et al 2013).…”
Section: Communicated By: Pamela Cecile Rasmussenmentioning
confidence: 99%
“…Third, aggression may influence paternity gain and loss if it is coupled with ejaculate quality (Rojas Mora et al 2017), mate guarding and/or copulation frequency (Ophir et al 2005) and/or extrapair activity (Spoon et al 2007;van Oers et al 2008). Lastly, aggression may influence hatching and fledging success either via nest-site quality (see above), differential maternal allocation (Grenna et al 2014;Szász et al 2014) or paternal provisioning, which can be negatively related to aggression (Duckworth 2006;Mutzel et al 2013).…”
Section: Communicated By: Pamela Cecile Rasmussenmentioning
confidence: 99%
“…A link between courtship and parental behaviour of males is also suggested indirectly by several empirical studies that found behavioural traits to play roles in mate choice (Otter and Ratcliffe 1996;Ophir and Galef 2003;Ophir et al 2005;Kunc et al 2006), differential allocation (Gwinner and Schwabl 2005;Grenna et al 2014) or sex allocation (Ramsay et al 2003;Szász et al 2014).…”
Section: Communicated By K Van Oersmentioning
confidence: 81%
“…From April to June, the hens laid a mean of 27.9 eggs, with a total of 5,209 eggs throughout the eight years. Most of the eggs laid were incubated for 26 days in a commercial incubator at 37.5 °C and 60% humidity, while 622 eggs (100 in 2002, 169 in 2003, 267 in 2005, and 86 in 2011) were brought to the lab for chemical analyses, and were analysed for concurrent studies (Cucco et al, 2012;Grenna et al, 2014).…”
Section: Methodsmentioning
confidence: 99%